2019
DOI: 10.35940/ijitee.i7530.078919
|View full text |Cite
|
Sign up to set email alerts
|

Polytechnic ESL Lecturers’ Acceptance of using Massive Open Online Course (MOOC) for Teaching English As A Second Language (ESL)

Abstract: The implementation of Massive Open Online Courses (MOOC) in the educational field has become the way of learning in many educational institutions worldwide. MOOC is believed could help to promote active learning among language learners. In Malaysian polytechnic settings, MOOC has just recently implemented for the English course. Thus, this study aimed to investigate polytechnics English as a Second Language (ESL) lecturers' acceptance of using Massive Open Online Course for teaching ESL and the challenges they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Hence, the principle of the UTAUT's core components of performance expectancy, effort expectancy, social influence and facilitating conditions may be undermined. This current finding corroborates what Sife et al (2007), as well as Rubaai and Hashim (2019) pointed out: that systemic challenges and limited skills required for the integration and implementation of e-learning, occasioned by a lack of technical support, prevents the effective usage of e-learning in various HEIs. Makgato (2014) also remarked that a lack of substantial support and assistance from the technical department is a major hurdle that prevents effective and efficient usage of e-learning facilities in various HEIs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, the principle of the UTAUT's core components of performance expectancy, effort expectancy, social influence and facilitating conditions may be undermined. This current finding corroborates what Sife et al (2007), as well as Rubaai and Hashim (2019) pointed out: that systemic challenges and limited skills required for the integration and implementation of e-learning, occasioned by a lack of technical support, prevents the effective usage of e-learning in various HEIs. Makgato (2014) also remarked that a lack of substantial support and assistance from the technical department is a major hurdle that prevents effective and efficient usage of e-learning facilities in various HEIs.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, the participants of this study indicated that just a few days of training were not sufficient to build the required skills and confidence they needed to use Moodle and other e-learning apparatus effectively. This finding supports the earlier submissions of Bagarukayo and Kalema (2015); Fresen (2011); Rubaai and Hashim (2019); and Sife et al (2007), who all stated that adequate training and retraining of academics is one of the enormous challenges facing the effective use of e-learning.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, most of online platforms offer educational content in English, which once again confirms its importance as an international language. MOOC are characterized by the following general advantages: independence from geographical location, economic advantage (free or minimal payment for online learning) [17,19]; self-paced character of taking the online course [5,16]; an opportunity to get higher education; development of additional competences that will be needed in professional activity [15]; an opportunity to receive a certificate after successful completion of the course. According to S. W. Chong, the advantage of MOOC is a wide selection of online courses which are focused on different levels of student training [29].…”
Section: B Key Features Of Using Mooc In Language Learningmentioning
confidence: 99%
“…The second group of research includes the works by Gilliland and Oyama et al [17], Uchidiuno [18], which analyze the design of online courses and the video content. The next group of research concerns the experience of using LMOOC by teachers, which is demonstrated in the works by Rubaai and Hashim [19], Len-Urritia and Cobos et al [20]. Also, this group includes the research by Meri-Yilan [21], Duru and Sunar et al [22], Dogan and Sunar et al [23], which demonstrates the experience of using LMOOC by students, taking online courses depending on their previous language training.…”
mentioning
confidence: 96%
“…Oyedemi (2012), also averred that the unavailability of Internet access. Al-Musa and Al-Mubarak (2005), add continuous updating to keep pace with developments in curricula, lack of incentives for the educational environment, loss of the human factor in education, the possibility of penetrating e-learning sites, lack of recognition of some Countries with certificates obtained by e-learning graduates, as well as Rubaai, and Hashim (2019) pointed that systemic challenges and limited skills occasioned by a lack of technical support, prevents the effective usage of e-learning in various HEIs. 9.1.5 Mathematics and Its Learning thereof Aqeelan (2002), stated that mathematics is "an abstract science of the creation and creativity of the human mind and is concerned with, among other things, the sequence of ideas, methods, and patterns of thinking.…”
Section: Obstacles To Using E-learningmentioning
confidence: 99%